Conclusions by analogy and their place in diagnostics - E. M. Doon (Бюллетень сибирской медицины)
In the article the main point of conclusions by analogy as a kind of logical reasoning and their cognitive value are analyzed. The place of these conclusions in doctor’s thinking is examined. And a criticism of wrong evaluation of conclusions in the diagnosis theory is given.